Extended Meaning of Prophet and Prophecy: Reviewing â€œNew Shelterâ€ of Ahmadiyyah and Mormonism - Ja'far, Ali (DINIKA : Academic Journal of Islamic Studies, 2018)
This study looks at the contemporary phenomena of the birth of two religions within Islam and Christianity, namely Ahmadiyyah and Mormonism. Through the frame of world religion classification, this study emphasizes what makes these sects become and classified by many scholars as ‘New Religions’ while other sects are not. This study re-looks at how hybrid religions have been crafted, developed and classified based on the age of the religion and where those religions first appeared, this study also looks at the historical process of how these hybrid religions became new religions. By considering the historical process, understanding prophecy, religious teaching, believe and particular interpretation over the main religions, this study aims to understand the emergent process of ‘new religions’ as temporary shelters for illegitimate sects. By comparing two sects, I conclude that these new religions have some common grounds which can be seen through interpreting the meaning of ‘prophet’ and ‘prophecy’, religious entities that make these sects excluded from the big umbrellas they are under Islam and Christianity. Keywords:Religion, Sect, Prophet, Prophecy